Keterampilan Berpikir Kritis Siswa SMA Melalui Implementasi Kurikulum Merdeka pada Pembelajaran Kimia - Galuh Pratiwi, Dian; Hadisaputra, Saprizal; Syarifa Wahidah Al Idrus (FKIP University of Mataram, 2024)
This study aims to describe students' critical thinking skills in learning chemistry through the use of Merdeka Curriculum at MAN 2 Kota Bima. This study used a descriptive quantitative approach, with a population of all class X students totaling 420 people and a research sample of 81 people selected by systematic random sampling. Data collection includes test questions and interviews. The findings show that: first, with respect to their overall performance in chemistry lessons, grade X students show a moderate category in terms of developing critical thinking skills. Second, students demonstrate proficiency across key indicators such as evaluation, interpretation analysis and conclusion development during lessons on subjects containing chemical principles. Third, the implementation of Merdeka curriculum in chemistry learning has not been carried out according to the stages mapped to implement detailed procedures that are inclusive in the outline made to prepare learning materials.